The occurrence, enzymatic production, and application of ethyl butanoate, an important flavor constituent. (17th August 2020) - Xu, Youqiang; Minhazul, Karim A. H. M.; Li, Xiuting
Abstract: Ethyl butanoate is well known for its value as a flavor chemical in food industries. It is naturally present in many fermented foods and with a rapid increase in demand. Studies are trying to improve its biological production as the method has advantages over direct extraction or chemical production in the way of cost, time, and product acceptance being natural. A total of twenty‐four studies have been published in the last three decades and used lipase from different sources as biocatalyst. Esterification of butanoic acid and ethanol as the precursors are reported in most of the studies with water as the by‐product and commonly recognized as a green route. As organic solvents increase the cost and may bring negative effects to the environment, the solvent‐free reaction system is recognized as a good alternative. However, hardly any works have been found on ethyl butanoate production in a water‐based reaction system and only a few studies focus on the biphasic and solvent‐free systems, while these systems have some attractive advantages over organic solvent‐based ester production. In addition, reviews related to this area are rare; therefore, this review summarizes the pathways to produce the ethyl butanoate in nature and the enzymatic production using different reaction systems. This will help to steerage the future research scope for improvement of ethyl butanoate production. Abstract : Ethyl butyrate synthesis through enzyme catalysis.